Transcriptome Analysis of Gills Provides Insights Into Translation Changes Under Hypoxic Stress and Reoxygenation in Golden Pompano, Trachinotus ovatus (Linnaeus 1758) - San, Lize; Liu, Baosuo; Liu, Bo; Guo, Huayang; Guo, Liang; Zhang, Nan; Zhu, Kecheng; Jiang, Shigui; Zhang, Dianchang (Frontiers in Marine Science, 2021)
Golden pompano (Trachinotus ovatus) is one of the most economically critical marine fishes in South China. Low oxygen stress, which is caused by various factors, has resulted in substantial economic losses to the aquaculture of T. ovatus. However, the molecular responses in fish gills to the hypoxia challenge remain unclear. To understand the mechanism adapted to hypoxia, we analyzed the transcriptome of T. ovatus gill in response to hypoxia stress for different durations. In this study, three groups were divided into normal oxygen group, hypoxia stress group and hypoxia treatment after oxygen recovery group. The hypoxic group included four different treatment times, and the recovery dissolved oxygen group included two different treatment times. Compared to the normoxia group, a total of 5294 genes were identified as differentially expressed genes. The number of down-regulated genes is more than the number of upregulated genes. After 8h of hypoxic treatment, the number of differential genes peaked, suggesting that 8h of hypoxic stress was a critical moment. According to kyoto encyclopedia of genes and genomes (KEGG) pathway analysis, many differential genes were enriched in steroid biosynthesis, focal adhesion, ECM-receptor interaction signal pathway, MAPK signal pathway and carbohydrate metabolism. In this study, it was found that genes related to cytokines such as chemokines, chemokine receptors, interleukin and complement were all significantly down-regulated, which may be the reason why fish are susceptible to pathogen infection under hypoxia environment. In addition, a large number of upregulated genes related to phagocytosis and protein degradation were found in the dissolved oxygen recovery group compared with the hypoxic treatment group for 24h. These results indicated that after the recovery of dissolved oxygen, the fish body quickly cleared the misfolded protein and repaired the damage through the endoplasmic reticulum stress and other pathways. These findings deepened the understanding of the hypoxia response mechanism of fish and provided a useful resource for the genetic breeding of T. ovatus.